DYPHTERIA IN TEHRAN, CAPITAL OF IRAN - N. Taghavi (Tehran University of Medical Sciences, 1976)
This is clinical and epidemiological study of 101 cases of diphtheria patients. 44 of these patients were male and 57 female. The majority of patients were 6 to 10 years old. Winter with 45% of all the cases had the highest seasonal incidence. The common symptoms were sore throat and false membrane in either one or both side of the throat. 50% of the patients had complication and '24% died because of the disease. Palatal paralysis was seen in 35% of the cases and was fully recovered. The worst complication was myocarditis, which was seen in 25% of the cases, and accounted for 50 % of the deaths. Altogether 24 patients died of disease 11 male and 3 female. 62.5% of the deaths occurred in the first ten days of the disease. We can say that the first ten days are the most critical ones. In only 17% of the patients could a previous contact with a diphtheria case be determined. Previous immunization reduces the complications and death of diphtheria and of the 5 immunized cases only one developed palatal paralysis with early recovery. Finally most of the patients were from lower class families and were living in crowded parts of the city.